2015
DOI: 10.2147/dddt.s82724
|View full text |Cite
|
Sign up to set email alerts
|

Small-molecule BH3 mimetic and pan-Bcl-2 inhibitor AT-101 enhances the antitumor efficacy of cisplatin through inhibition of APE1 repair and redox activity in non-small-cell lung cancer

Abstract: AT-101 is a BH3 mimetic and pan-Bcl-2 inhibitor that has shown potent anticancer activity in non-small-cell lung cancer (NSCLC) in murine models, but failed to show clinical efficacy when used in combination with docetaxel in NSCLC patients. Our recent study has demonstrated that AT-101 enhanced the antitumor effect of cisplatin (CDDP) in a murine model of NSCLC via inhibition of the interleukin-6/signal transducer and activator of transcription 3 (STAT3) pathway. This study explored the underlying mechanisms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 96 publications
(188 reference statements)
0
4
0
Order By: Relevance
“…Nuclear Bcl-xL also plays an important role in DNA damage. Nuclear Bcl-xL can inhibit the DNA damage repair gene APE1 by interacting with APE1, thus enhancing oncotherapy-induced DNA damage and apoptosis 30 . This suggests that not only total Bcl-xL levels but the distribution of Bcl-xL are also an important factor in oncotherapy-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Nuclear Bcl-xL also plays an important role in DNA damage. Nuclear Bcl-xL can inhibit the DNA damage repair gene APE1 by interacting with APE1, thus enhancing oncotherapy-induced DNA damage and apoptosis 30 . This suggests that not only total Bcl-xL levels but the distribution of Bcl-xL are also an important factor in oncotherapy-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that obatoclax (GX15–070) induces apoptosis and enhances cisplatin-induced apoptosis in NSCLC cells [ 38 ]. Ren et al [ 39 ] reported that (−)-Gossypol enhances the antitumor efficacy of cisplatin through inhibition of APE1 repair and redox activity in non-small cell lung cancer. Furthermore, synergistic antitumor effects have been observed when MCL-1 inhibitors combined not only with cytoxic drugs but also with other chemotherapeutic agents.…”
Section: Discussionmentioning
confidence: 99%
“…For example, E3330 (an NF-κB inhibitor) and Gossypol/AT101 (BCL2 inhibitors) can bind APE1 making it less redox active [ 45 , 46 ]. These agents can induce cytotoxicity as single agents [ 47 ] or in combination [ 46 , 48 ] in lung, lymphoma, prostate, adrenocortical and glioblastoma cancers, and more than 20 clinical trials are currently investigating their suitability.…”
Section: Inhibitors To the Ber Enzymesmentioning
confidence: 99%